The Effectiveness of Bank Credit Management On Risk Reduction in Palestinian Banks: Applied Study on Bank of Palestine - Al-Silwadi, Abdelrahman; Masharqa, Odah (The Arab Journal of Administration, 2020)
The purpose of this study is to investigates the effectiveness of bank credit management, and the impact of credit analysis on credit risks reduction in commercial banks operating in the Palestinian territories, taking into account the role of the main factors of credit risk analysis, namely the borrower’s personality, purpose of the loan, borrower’s intentions (ability and willingness), required collateral and prospects. The study ultimate goal is to reduce the credit risk in commercial banks operating in Palestine in general and the Bank of Palestine in particular. The researchers developed a tool to collect the required data (questionnaire), which was verified and validated. The questionnaire was then distributed to a sample of 35 employees of the Bank of Palestine in Ramallah, representing 86% of the study population. After data collection, coding and entering the collected data into the computer, using the SPSS statistical package, a simple linear regression test was used to measure the impact of independent variables; the borrower’s personality, purpose of the loan, borrower’s intentions, required collateral and prospects on credit risk reduction. The results indicated that there was a significant impact of the five dimensions of the credit management on the reduction of credit risk, with the value of the coefficient of determination (R2) 0.60. Analysis of borrower’s intentions (ability and willingness) to has been ranked first in terms of importance in reducing credit risk. The results also found NO significant differences among the study sample due to (type of credit, years of experience and qualification). Meanwhile differences were found in the variables of branch managers and the employees of credit department.